2021
DOI: 10.1101/2021.07.26.453840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protection of human ACE2 transgenic Syrian hamsters from SARS CoV-2 variants by human polyclonal IgG from hyper-immunized transchromosomic bovines

Abstract: Pandemic SARS CoV-2 has been undergoing rapid evolution during spread throughout the world resulting in the emergence of many Spike protein variants, some of which appear to either evade antibody neutralization, transmit more efficiently, or potentially exhibit increased virulence. This raises significant concerns regarding the long-term efficacy of protection elicited after primary infection and/or from vaccines derived from single virus Spike (S) genotypes, as well as the efficacy of anti-S monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…In a few studies, however, the viral reduction factor reached 3 or 4 log (33,(42)(43)(44)(45). Interestingly, Gilliland et al (22) reported the absence of viral reduction in the lung of SARS-CoV-2 challenged mice treated with a humanized cow polyclonal antibody, whereas a clear clinical impact was demonstrated. One limitation of our model in which mice airways are transduced with an adenovirus expressing human ACE-2 is the absence of clinical symptoms, as the mice eliminate the virus by themselves within a few days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a few studies, however, the viral reduction factor reached 3 or 4 log (33,(42)(43)(44)(45). Interestingly, Gilliland et al (22) reported the absence of viral reduction in the lung of SARS-CoV-2 challenged mice treated with a humanized cow polyclonal antibody, whereas a clear clinical impact was demonstrated. One limitation of our model in which mice airways are transduced with an adenovirus expressing human ACE-2 is the absence of clinical symptoms, as the mice eliminate the virus by themselves within a few days.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the Beta lineage (K417N, E484K, and N501Y in RBD), especially mutations of Spike at E484 but also in the Nterminal domain (NTD; L18F, D80A, D215G, D242-244, and R246I in SA variant (10,11)), reduce neutralization sensitivity or confer neutralization escape from multiple mAbs (4,5,(12)(13)(14)(15)(16)(17)(18)(19)(20). Third, polyclonal antibodies produced in their Fab'2 format from horses (21) or in their IgG format from humanized cows (22) or glyco-humanized pigs (23) have also proven efficacy to neutralize SARS-CoV-2. The safety and tolerability in humans of Fab'2 from horses and of humanized IgG polyclonal antibodies have been confirmed recently in different clinical trials (Lopardo et al, 2021 (21), NCT04453384, NCT04469179, Gaborit et al, 2021 (24)), contrasting with unmodified polyclonal antibodies containing wild-type IgG antibodies that induce serum sickness and allergic reactions (including fever and skin rashes) in 20% to 30% of the patients, excepting for those who concomitantly receive immunosuppression and high doses of steroids (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…In a few studies, however, the viral reduction factor reached 3 or 4 log 33,[42][43][44][45] . Interestingly, Gilliland et al 22 reported absence of viral reduction in the lung of SARS-CoV-2 challenged mice treated with a humanized cow polyclonal antibody, whereas a clear clinical impact was demonstrated. One limitation of our model in which mice airways are transduced with an adenovirus expressing human ACE-2 is the absence of clinical symptoms, as the mice eliminate the virus by themselves within a few days.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the Beta lineage (K417N, E484K, and N501Y in RBD), especially mutations of Spike at E484 but also in the N-terminal Domain (NTD; L18F, D80A, D215G, Δ242-244, and R246I in SA variant 10,11 ) reduce neutralization sensitivity or confer neutralization escape from multiple mAbs 4,5,[12][13][14][15][16][17][18][19][20] . Third, polyclonal antibodies produced in their Fab'2 format from horses 21 or in their IgG format from humanized cows 22 or glyco-humanized pigs 23 have also proven efficacy to neutralize SARS-CoV-2. The safety and tolerability in humans of Fab'2 from horses and of humanized IgG polyclonal antibodies has been confirmed recently in different clinical trials (Lopardo et al, 2021 21 , NCT04453384, NCT04469179, Gaborit et al, 2021 24 ), contrasting with unmodified polyclonal antibodies containing wild-type IgG antibodies that induce serum sickness and allergic reactions (including fever and skin rashes) in 20 to 30% of the patients, excepting for those who concomitantly receive immunosuppression and high doses steroids 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…This affords polyclonal antibodies a distinct advantage over monoclonal antibodies when used as therapeutic agents particularly in patients infected with rapidly mutating SARS-CoV-2 virus. immunoglobulin produced in transchromosomic bovines (Tc-hIgG-SARS-CoV-2) hyperimmunized with two doses of plasmid DNA encoding the SARS-CoV-2 Wuhan strain S gene, followed by repeated immunization with S protein purified from insect cells (6,7). The resulting Tc-hIgG-SARS-CoV-2, termed SAB-185, efficiently neutralizes SARS-CoV-2, and vesicular stomatitis virus (VSV) SARS-CoV-2 chimeras in vitro.…”
mentioning
confidence: 99%